Islamic Values of Social Relation in Besaprah Tradition of Sambas Society: The Case of Post-Conflict Malay-Madura in 1999-2017 - Abdul Wahab (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This paper discusses the effects of inter-ethnic conflict in 1999 on the social life in Sambas. Therefore, any effort dealing with post-conflict situation is needed, through the concept of Islamic character education to modify the Besaprah local wisdom in Malay-Sambas society. This study used a qualitative method with an ethnographic approach which tries to interpret the phenomena in Sambas society since the post-conflict of Malay-Madura in 1999. The research findings show that the inter-ethnic conflict in Sambas, West Kalimantan, occurring in 1999 led to some problems, i.e. moral and social problem, as well as the crisis of local wisdom values. Accordingly, empowering local wisdom values in Besaprah tradition has a contribution to Islamic education concept as it gives an alternative solution to cope with negative effects of the inter-ethnic conflict.